Synthesis and Spectral Investigation (1H and 13C) of Tetradentate Schiff Base Ligands for the Preparation of Post Transition Bimetallic Complexes of Antimicrobial Importance - Fawad Zahoor, Ameer; Yousaf, Muhammad; Pervaiz, Muhammad; Anjum, Anbreen; Ghulam Ali, Kulsoom; Maqbool Zahid, Faisal; Ahmad, Sajjad; Anwer Bukhari, Shazia; Parveen, Bushra (Asian Journal of Chemistry, 2014)
A tetradentate Schiff base ligand 2-(bis-2-hydroxylphenylidene)-1,2-diiminoethanne (L) was synthesized and then its structure was investigated by 1H NMR and 13C NMR techniques. The ligand and its bimetallic complexes were screened in vitro for antibacterial and antifungal activities by using disc diffusion method. The results showed that in case of antibacterial activity the Co2L2 exhibited better efficiency (9 ± 0.816) against E. coli while binuclear complex of Mn2L2 showed better potential against all the three strains (E. coli, S. aureus and A. alternate) as compared with other attempted bimetallic (Cu, Mn and Zn) complexes when compared with standard one. Similarly the antifungal potential of binuclear (Co2L2) complex was satisfactory (12.25 ± 0.062) for A. alternate while the binuclear Cu2L2 complex exhibited good effect (7.75 ± 0.957) against A. niger. Similarly binuclear Mn2L2 complex showed better efficiency (10.25 ± 0.5) against A. flavous. The biological activity data justified that binuclear post transition metal complexes with Schiff base can be successfully used against fungal as well as bacterial infections.